Inhibition of the fungus Colletotrichum lindemuthianum in the presence of different potassium sorbate concentrations - Engel, Fernanda; Azeredo Coutinho Neto, Antônio (Revista Agrogeoambiental, 2021)
One of the major problems of in vitro plant cultivation is caused by contaminations such as fungal, which represent great losses for plant cultivation laboratories. In view of the problem about contamination and gaps in efficient disinfection protocols, the present study aimed to evaluate the inhibition of the fungus Colletotrichum. lindemuthianum in the presence of the potassium sorbate food preservative at different concentrations (0 g L-1; 0.076 g. L-1; 0.15 g. L-1; 0.30 g. L-1; 0.45 g. L-1; 0.60 g. L-1 and 0.75 g. L-1). The analyses of the Percentage of Micelal Growth Inhibition (ICP) and the growth at 24 and 72 hours at different concentrations were quantified. It was observed that Potassium Sorbate was effective in the analysis of ICP at different concentrations in relation to control, with greater effectiveness for T4 to T7. The highest percentages of inhibition (T5 to T7) presenting an inhibition rate of mean mycelial growth of 17.5 % in relation to the control for the 72h period, indicating, therefore, that with further studies this preservative can be used to combat fungal microorganisms in vitro culture.